On the determination of the Carrying Capacity of an Ice Cover for Loads of Long Duration (K Raschety Gruzpodbemnosti Ledyanogo Pokrova pri Stoyanke Gruzov na Lyd) - Panfilov,D. F. (1972)
In hydraulic engineering operations from ice, loads can remain on the ice cover for an extended period of time. It is of practical interest to establish the permissible time of the loads' standing on the ice and estimate its load-bearing capacity at any time after the application of the load. In the article, the author discusses a solution to this question on the basis of contemporary data on the plastic properties of ice. Draft trans. of Izvestiya Vyashikh Uchebnykh Zavedenii. Stroitelstvo i Arkhitektura (USSR) n6 p47-57 1961.